Chrysanthemum expressing a linalool synthase gene 'smells good', but 'tastes bad' to western flower thrips. Issue 7 (7th June 2013) - Yang, Ting; Stoopen, Geert; Thoen, Manus; Wiegers, Gerrie; Jongsma, Maarten A.
Summary Herbivore‐induced plant volatiles are often involved in direct and indirect plant defence against herbivores. Linalool is a common floral scent and found to be released from leaves by many plants after herbivore attack. In this study, a linalool/nerolidol synthase, FaNES1, was overexpressed in the plastids of chrysanthemum plants (Chrysanthemum morifolium). The volatiles of FaNES1 chrysanthemum leaves were strongly dominated by linalool, but they also emitted small amount of the C11‐homoterpene, (3E)‐4, 8‐dimethyl‐1, 3, 7‐nonatriene, a derivative of nerolidol. Four nonvolatile linalool glycosides in methanolic extracts were found to be significantly increased in the leaves of FaNES1 plants compared to wild‐type plants. They were putatively identified by LC‐MS‐MS as two linalool–malonyl–hexoses, a linalool–pentose–hexose and a glycoside of hydroxy–linalool. A leaf‐disc dual‐choice assay with western flower thrips (WFT, Frankliniella occidentalis) showed, initially during the first 15 min of WFT release, that FaNES1 plants were significantly preferred. This gradually reversed into significant preference for the control, however, at 20–28 h after WFT release. The initial preference was shown to be based on the linalool odour of FaNES1 plants by olfactory dual‐choice assays using paper discs emitting pure linalool at similar rates as leaf discs. The reversal of preference into deterrence could be explained by the initial nonvolatile composition of the FaNES1 plants, as methanolic extracts were less preferred by WFT. Considering the common occurrence of linalool and its glycosides in plant tissues, it suggests that plants may balance attractive fragrance with 'poor taste' using the same precursor compound.